1999
DOI: 10.1086/314905
|View full text |Cite
|
Sign up to set email alerts
|

The Mumps Virus Neurovirulence Safety Test in Rhesus Monkeys:A Comparison of Mumps Virus Strains

Abstract: Wild type mumps viruses are highly neurotropic and a frequent cause of aseptic meningitis in unvaccinated humans. To test whether attenuated mumps viruses used in the manufacture of mumps vaccines have neurovirulent properties, a monkey neurovirulence safety test (MNVT) is performed. However, results with several mumps virus MNVTs have raised questions as to whether the test can reliably discriminate neurovirulent from nonneurovirulent mumps virus strains. Here, various mumps virus strains representing a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Preventing infected cells from dying or from dying prematurely is beneficial to virus replication. Interestingly, it has been reported that increased CPE induced by mumps virus infection in vitro (tissue culture cells) seems to correlate with decreased pathogenicity of the virus in a rat model system (35)(36)(37)(38). Not surprisingly, a mutation in SV5 causing increased CPE in infected cells results in a mutant that is attenuated in vivo (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Preventing infected cells from dying or from dying prematurely is beneficial to virus replication. Interestingly, it has been reported that increased CPE induced by mumps virus infection in vitro (tissue culture cells) seems to correlate with decreased pathogenicity of the virus in a rat model system (35)(36)(37)(38). Not surprisingly, a mutation in SV5 causing increased CPE in infected cells results in a mutant that is attenuated in vivo (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Mumps virus neurovirulence testing as currently performed in monkeys has failed to discriminate between strains with known differences in human neurovirulence (2,8,27,28). Similarly, tests in hamsters have also failed to reliably discriminate neurovirulent from nonneurovirulent human mumps virus strains (12,19,22,34).…”
mentioning
confidence: 99%
“…Recent reports have indicated that the monkey neurovirulence test (MNVT) is not sufficiently predictive of mumps virus neurovirulence in humans (2,27). However, based on the observed influence of virus dose on RNVT scores, it was conceivable that the use of higher or lower doses of mumps virus might yield responses in monkeys better correlating with neurovirulence in humans.…”
mentioning
confidence: 99%
“…Any live viral vaccines for human use must pass the neurovirulence test in nonhuman primates (16)(17)(18)(19). In order to take advantage of live rVSVs as a vaccine vector for their high yield and for their induction of strong and long-lasting immune responses, it is necessary to make the live vaccine vector safe to use in humans without losing its immunogenicity.…”
Section: Esicular Stomatitis Virus (Vsv) Is a Rapidly Replicating Vmentioning
confidence: 99%